The Curse of Irving Fisher (Professional Forecasters' Version) - Gregor W. Smith; James Yetman (Queen's University, Department of Economics, 2007)
Dynamic Euler equations restrict multivariate forecasts. Thus a range of links between macroeconomic variables can be studied by seeing whether they hold within the multivariate predictions of professional forecasters. We illustrate this novel way of testing theory by studying the links between forecasts of U.S. nominal interest rates, inflation, and real consumption growth since 1981. By using forecast data for both returns and macroeconomic fundamentals, we use the complete cross-section of forecasts, rather than the median. The Survey of Professional Forecasters yields a three-dimensional panel, across quarters, forecasters, and forecast horizons. This approach yields 14727 observations, much greater than the 107 time series observations. The resulting precision reveals a significant, negative relationship between consumption growth and interest rates.
Keywords: E17; E21; E43; 330; forecast survey; asset pricing; Fisher effect; Wirtschaftsprognose; Zins; Inflationsrate; Privater Konsum; Fisher-Effekt; USA